Avaliação da segurança hídrica no Vale do Forquilha, semiárido cearense - Moreira, Adrissa Figueiró (2024)
Water security can be understood as the guarantee of water in quantity and quality that is adequate for the subsistence of life and human well-being. However, access to safe and reliable water is associated with the model of sanitation services, water management, deficiencies in planning and technical choices, as well as the way in which existing systems operate. This fact is amplified in the face of climate change scenarios, especially for arid and semi-arid areas of developing countries. This research aims to analyze water security through the Global Household Water Insecurity Scale (HWISE) and its correlations in the perception of residents of Vale do Forquilha, relating them to the hydrosocial context in the semi-arid region of Ceará. To this end, we start from a qualitative and quantitative approach external to the understanding of issues related to water for domestic activities, as well as other variables that influence obtaining water. The results indicate that cisterns are an effective alternative for accessing water in the semiarid region, providing an efficient way of storing water. The Household Water Insecurity Scale allowed both the identification of determinants and the assessment of the consequences of Household Water Insecurity (HWI). It involves health, economic and psychosocial contexts, including Food Insecurity, favoring the identification of vulnerable populations within communities. In this way, the HWI classes that provide an understanding of water uncertainty at the local level in the Brazilian semiarid scenario were defined and characterized.